Pandemic treaty as an instrument to strengthen global health security: Global health diplomacy at its crux - Vijay Kumar Chattu; Rajani Mol; Bawa Singh; K. Srikanth Reddy; Arian Hatefi (Health Promotion Perspectives, 2024)
Background: The World Health Assembly (WHA), on 1st December 2021, unanimously agreed to launch a global process to draft and negotiate a convention, agreement, or other international instrument under the World Health Organization’s (WHO’s) constitution to strengthen pandemic prevention, preparedness, and response. We aimed to explore the role of global health diplomacy (GHD) in pandemic treaty negotiations by providing deep insight into the ongoing drafting process under the WHO leadership. Methods: We conducted a narrative review by searching Scopus, Web of Sciences, PubMed, MEDLINE, and Google Scholar search engine using the keywords "Pandemic Treaty," OR "International Health Regulations," OR "International conventions," OR "International treaties" in the context of recent COVID-19 pandemic. Besides, we included articles recommending the need for GHD, leadership and governance mechanisms for this international treaty drafting approved by the WHA. Results: Amid the COVID-19 pandemic, the concept of GHD bolstered the international system and remained high on the agendas of many national, regional and global platforms. As per Article 19 of the WHO constitution, the Assembly established an intergovernmental negotiating body (INB) to draft and negotiate this convention/ agreement to protect the world from disease outbreaks of pandemic potential. Since GHD has helped to strengthen international cooperation in health systems and address inequities in achieving health-related global targets, there is a great scope for the successful drafting of this pandemic treaty. Conclusion: The pandemic treaty is a defining moment in global health governance, particularly the pandemic governance reforms. However, the treaty’s purpose will only be served if the equity considerations are optimized, accountability mechanisms are established, and a sense of shared responsibility is embraced. While fulfilling treaty commitments might be complex and challenging, it provides an opportunity to rethink and build resilient systems for pandemic preparedness and response in the future.